Factors related to the place of first choice for the diagnosis of tuberculosis - Dândara Nayara Azevêdo Dantas; Bertha Cruz Enders; Ana Angélica Rêgo de Queiroz; Alexsandro Silva Coura; Marcela Paulino Moreira da Silva; Rejane Maria Paiva de Menezes
The objective of this study was to identify factors related to the place of first choice for the diagnosis and treatment of tuberculosis. A descriptive quantitative study was conducted in Natal/RN, throughout February/September 2012 with 60 individuals diagnosed with pulmonary tuberculosis that responded a questionnaire. Data were analyzed by the Chi-square and Fisher test. The factors associated to the place of first choice were: having had previous contact with the disease (p=0,04); the person's awareness of the disease (p=0,018) and having had previous care at the health service unit of choice (p=0,002). It is concluded that intrinsic and extrinsic factors may influence the individual's first choice of a place for care and diagnosis of diseases. It is important that nurses promote actions related to these factors, for the enhancement of early diagnosis of tuberculosis through case finding and access to the primary care unit thereby reducing the demand for emergency services.